I shall sing these songs beautifully - Lanthimos, Giōrgos 1973- (MACK, 2024)
"Yorgos Lanthimos's filmography, lauded for its ambitious world-building and absurdist explorations of human relations, has established him as one of the most distinctive auteurs in contemporary cinema. ' i shall sing these songs beautifully' draws on his renowned visual language to tell a haunting new story through photographs Lanthimos made on the set of his latest feature, 'Kinds of Kindness' (2024), inhabiting an ambiguous space between the real locations of New Orleans and the otherworld of cinema. Interwoven throughout are new texts by Lanthimos which evoke the fragmented lyricism of Sappho, from whose poetry the book takes its title. Lanthimos makes all his photography, both still and moving, on analogue film, relishing the creative intimacy the medium involves. These previously unseen colour and black-and-white images became a part of the formation of his new film's world. Here, they become fragments that elaborate an entirely new story, rich with the tensions and unsettling atmospheres that Lanthimos has made his own."--Publisher's web site for this work https://mackbooks.co.uk/collections/mack/products/i-shall-sing-these-songs-beautifully-yorgos-lanthimos
Impressum: All photographs were taken in and around New Orleans in 2022
Keywords: Lanthimos, Giōrgos -- 1973-; Geschichte 2022; Fotografie; New Orleans -- La., Motiv; Photography, Artistic; Photographie artistique; art photography; photobooks; Photobooks; Livres de photographies; New Orleans (La.) / Pictorial works; Bildband